Atrial natriuretic peptide inhibits epithelial-mesenchymal transition (EMT) of bronchial epithelial cells through cGMP/PKG signaling by targeting Smad3 in a murine model of allergic asthma. (14th September 2019) - Chu, Shuyuan; Zhang, Xiufeng; Sun, Yabing; Liang, Yaxi; Sun, Jingyi; Lu, Minyan; Huang, Jianwei; Jiang, Ming; Ma, Libing
Abstract: Background: Atrial natriuretic peptide (ANP) inhibits TGF-β1-induced epithelial-mesenchymal transition (EMT) in human airway cells. We aim to explore the role and mechanism of ANP on EMT of bronchial epithelial cells from murine model of allergic asthma in vitro.Methods: Murine model of allergic asthma was established with BALB/c mice using ovalbumin (OVA). Bronchial epithelial cells were isolated from OVA-exposed mice, and then were cocultured with TGF-β1, ANP, natriuretic peptide receptor A antagonist, cGMP analog, cGMP inhibitor or/and protein kinase G (PKG) inhibitor, respectively. We assessed expressions of E-Cadherin, α-SMA, cGMP, Smad3 and p-Smad3 in the murine cells before and after Smad3 silence.Results: Compared with bronchial epithelial cells from controls and OVA-exposed mice without additional stimulation, the mRNA and protein expressions of E-Cadherin were decreased but α-SMA expressions were increased in cells with TGF-β1 stimulation from OVA-exposed mice in vitro. That could be reversed by ANP. The effect of ANP could be mimicked by the cGMP analog, which could be reversed by cGMP or PKG inhibitor. Moreover, the phosphorylated Smad3 expression was consistent with that of α-SMA. When Smad3 was silenced, Smad3 was mostly expressed in cytoplasm. In contrast, it is mostly expressed in nucleus of non-silenced cells during EMT.Conclusions: In a murine model of allergic asthma, ANP could inhibit TGF-β1-induced EMT of bronchial epithelial cells through cGMP/PKG signaling, targeting TGF-β1/Smad3 via attenuating phosphorylation of Smad3 in vitro, which may provide potential of ANP in treating allergic asthma with airway remodeling.